Notes on an overlooked Paepalanthus (Eriocaulaceae) from central Brazil: identity, taxonomic placement, and morphological details - Da Silva, Lucas Espindola Florêncio; Trovó, Marcelo (Phytotaxa, 2020)
Paepalanthus canescens var. atratus was described from a single collection of juvenile individuals. We have recently rediscovered new populations of this taxon, and here describe the flowers for the first time. The vegetative and floral morphology of this taxon does not fit the P. canescens concept, nor does the taxon share the characters defining P. subsect. Actinocephaloides, to which P. canescens belongs. Here, we raise the taxon to species level, as P. atratus, and provide a revised description for it. We critically evaluate the taxonomy and morphology of the species, and compare it to Paepalanthus trichophyllus, the most similar species morphologically. Comments on distribution and conservation, as well as details of morphological variation, a distribution map, and photos, are provided.